[Newsletter regarding issues anti-smoking advocates are facing] (Tufts Archival Research Center, 2007)
Newsletter put out by Tobacco Free Washington, an anti-smoking advocacy group regarding the issues that anti-smoking groups are facing. Includes enforcing smoking bans, secondhand smoke and youth smoking.